2021
DOI: 10.1371/journal.pntd.0009036
|View full text |Cite
|
Sign up to set email alerts
|

The entomological impact of passive metofluthrin emanators against indoor Aedes aegypti: A randomized field trial

Abstract: Background In the absence of vaccines or drugs, insecticides are the mainstay of Aedes-borne disease control. Their utility is challenged by the slow deployment of resources, poor community compliance and inadequate household coverage. Novel application methods are required. Methodology and principal findings A 10% w/w metofluthrin “emanator” that passively disseminates insecticide from an impregnated net was evaluated in a randomized trial of 200 houses in Mexico. The devices were introduced at a rate of 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Extending findings observed for Ae . aegypti [ 33 ] we show that a 10% metofluthrin passive emanator has high potential to reduce human- Ae . albopictus contacts both indoors and outdoors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extending findings observed for Ae . aegypti [ 33 ] we show that a 10% metofluthrin passive emanator has high potential to reduce human- Ae . albopictus contacts both indoors and outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared to metofluthrin coils, passive emanators have significantly longer duration and the added benefit of not requiring burning or other source of heat. In Merida, Mexico, household surveys showed that people view very positively the use of metofluthrin emanators as alternative to coils and reported measurable reductions in mosquito bites after their use [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquitoes from Cairns WT, WB2, w AlbB2-F4 strains were tested for the presence of mutations in the voltage-gated sodium channel protein (VGSC) gene associated with knock down resistance to pyrethroids using Allele-specific quantitative PCR and melting curve analysis (AS-PCR) [54, 55]. These mutations included single nucleotide mutations causing changes from valine (V) to leucine (L) amino acid substitution at locus 410 (V410L), V to isoleucine (I) at locus 1016 (V1016I) and from phenylalanine (F) to cysteine (C) at position 1534 (F1534C) (numbered according to the homologous locus in the VCSC gene in Musca domestica ).…”
Section: Methodsmentioning
confidence: 99%
“…Current malaria vector control guidelines do not recommend the use of SRs for personal protection [16]. However, various SR products have been shown to reduce mosquito biting [17][18][19][20][21][22][23] and, in epidemiological studies conducted in Indonesia [24], China [25], and Peru [26] have been shown to reduce pathogen transmission in human populations.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%